Equality of Opportunity, Moral Hazard and the Timing of Luck - Arnaud Lefranc; Alain Trannoy (Institute of Labor Economics (IZA), 2017)
Equality of opportunity is usually defined as a situation where the effect of circumstances on outcome is nullified (compensation principle) and effort is rewarded (reward principle). We propose a new version of the reward principle based on the idea that effort deserves reward for it is costly. We show that luck can be introduced in two ways in the definition of these principles, depending on whether the correlation between luck and circumstances should be nullified and whether the correlation between luck and effort should be rewarded. In this regard, the timing of luck with respect to effort decisions is crucial, as is exemplified by moral hazard where effort choice influences the lottery of future uncertain events.
Keywords: D63; J62; C14; 330; equality of opportunity; effort; luck; timeline; moral hazard; reward